Nigerian higher education institutions performance: does strategic improvisation and entrepreneurial self-efficacy matter? - Ibrahim, Najafi Auwalu; Mahmood, Rosli; Bakar, Muhammad Shukri (Universiti Malaysia Perlis, 2016)
Global competition, dynamic environment; and the need for efficient and effective resource utilization have created a lot of pressure on today’s organisations including Higher Education Institutions (HEIs).Hence, the need for leaders capable of engaging in daring activities such as improvisation and entrepreneurial self-efficacy cannot be overemphasized.The objective of the study is to examine the relationship between leaders’ strategic improvisation, entrepreneurial self-efficacy and HEIs performance in Nigeria. Using a structured questionnaire to academic leaders in HEIs in Kano state, Nigeria a total of 220 useable data was gathered and analysed using SmartPLS 3.0. The result indicates that all the exogenous variables have a significant relationship with the endogenous variable of the study.Strategic improvisation and entrepreneurial self-efficacy explains 21.9% of the variance of HEIs performance.Interestingly, strategic improvisation was found to be the strongest predictor of HEIs performance in Nigeria.Finally, implications and suggestions for future studies were presented and elaborated.